Compositional properties of flours and starches from the Philippine National Seed and Industry Council - registered root crops - Tulin, Edgardo E. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2023)
Based in the Visayas State University, Philippines, the germplasm collection of the Philippine Root Crops Research and Training Center (PhilRootcrops) is home to several varieties that have not been fully characterized for their potential use in the production of functional foods. This study evaluated the compositional properties, amylose/amylopectin ratio, and glycemic index of flour and starches of 10 varieties of cassava (Manihot esculenta Crantz), sweet potato (Ipomoea batatas L. (Lam)), and taro (Colocasia esculenta L. Schott); 8 varieties of yam (Dioscorea alata L.); and 5 varieties of arrowroot (Maranta arundinacea L.), which was the recommended varieties of the National Seed and Industry Council (NSIC). The total starch as well as the amylose/amylopectin ratio of the starch component was determined using Megazyme assay kits, and the glycemic indices were predicted through enzymatic in vitro starch hydrolysis. Results revealed significant (p < 0.05) varietal variations on flour and starch yield, dry matter, crude protein, crude fiber, amylose/amylopectin ratio, and glycemic index. Among these crops, sweet potato was found to have the highest amylose contents, while taro and arrowroot showed lower glycemic indices. These profiles can serve as fundamental information for processors to develop new products that capitalize on these unique properties.